Insight Into Mouse Models of Hyperthyroidism - Zhang, Mengyu; Jiang, Wen; Lu, Ganghua; Wang, Ru; Lv, Zhongwei; Li, Dan (Frontiers in Endocrinology, 2022)
Hyperthyroidism is characterized by an increase in the synthesis and secretion of thyroid hormones in the thyroid gland, and the most common cause of overproduction of thyroid hormones is Graves’ disease (GD). Long-term disease models of hyperthyroidism have been established. In general, methods to induce GD include transfection of fibroblasts, injecting plasmids or adenovirus containing thyroid stimulating hormone receptor (TSHR) or TSHR subunit, and exogenous artificial thyroid hormone supplementation. Fortunately, in mouse studies, novel treatments for GD and Graves’ orbitopathy (GO) were discovered. It has been reported that prophylactic administration of TSHR A subunit protein in genetically susceptible individuals could induce immune tolerance and provide protection for the future development of GD. Biologically active monoclonal antibody against intracellular adhesion molecule-1 (ICAM-1 mAb) and siRNA targeting TSHR can also be used to treat GD. Moreover, new potential therapeutic targets have been identified in GO mouse models, and these targets could present novel therapeutic approaches. Besides, human placental mesenchymal stem cells (hPMSCs) into the orbit, fucoxanthin and icariin may be new alternative therapies that could be used in addition to the existing drugs, although further research is needed.